Facile synthesis of CuO/g-C3N4 nanolayer composites with superior catalytic reductive degradation behavior. (February 2023) - Suresh, R.; Karthikeyan, N.S.; Gnanasekaran, Lalitha; Rajendran, Saravanan; Soto-Moscoso, Matias
Abstract: The cupric oxide (CuO) loaded graphitic carbon nitride (g-C3 N4 ) nanocomposites (CuO/g-C3 N4 ) were prepared by a facile calcination method. The formation of monoclinic CuO nanocrystals along with g-C3 N4 was confirmed by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopic analysis. X-ray photoelectron spectral (XPS) analysis further confirms the formation of CuO/g-C3 N4 . Distribution of CuO stone-like crystalline nanoparticles on g-C3 N4 nanosheets was observed by transmission electron microscopic images. The influence of CuO loading on the optical property of g-C3 N4 was determined by ultraviolet (UV)-visible absorption and photoluminescence (PL) spectral analysis. Band gap was decreased from 2.7 to 2.3 eV by the addition of CuO nanoparticles. The catalytic performance of the synthesized samples in 4-nitrophenol (4-NP) and methyl orange (MO) reduction was evaluated. The 5 wt% CuO/g-C3 N4 showed 99.5% (7 min) and 99.7% (4 min) reduction efficiency for 4-NP and MO respectively. The 5 wt% CuO/g-C3 N4 could become a potential catalyst in the chemical treatment of organic pollutants. Graphical abstract: Image 1 Highlights: CuO loaded g-C3 N4 nanocomposites were prepared by one-step calcination method. 4-NP and MO catalytic reduction behavior of CuO/g-C3 N4 and pure CuO is better than g-C3 N4 . 5 wt% CuO/g-C3 N4 nanocomposite showed maximum catalytic efficiency and rate constant than other samples.